(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The unsteady freeconvective magnetohydrodynamic flow of an conducting visco elastic dusty fluid with transverse magnetic field and radiation confined by horizontal channel is considered. The influence of oscillatory pressuregradient and the movement of the top plate are incorporated. The heat generated is established in both motions of fluid and dust particles and is high enough to radiate heat. The solutions of velocity distribution, temperature distribution of the fluid, velocity and energy of the dust particle are achieved by employing perturbation scheme. The physical parameters involved in both profiles for fluid and dust particles are examined with aid of graph.